2017
DOI: 10.1002/slct.201701643
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reduction of Toxic Nitroarenes in Aqueous Medium Using Worm‐Like Rhodium Nanoparticles

Abstract: We demonstrate a facile synthesis of worm‐like rhodium nanoparticle stabilized by octadecylamine. This worm‐like nanoparticle exhibits excellent catalytic activity toward the reduction of nitro aromatics in the presence of NaBH4 in aqueous medium at room temperature. The reaction follows pseudo‐first order kinetics with a rate constant of 0.0216 s−1. We have explored this catalytic activity for the reduction of several nitro derivatives. This catalyst can effectively reduce toxic nitro aromatics in aqueous med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…5c), a similar to the trend observed for Pt nanoparticles. 78 As mentioned above, some reports revealed that CO oxidation on hcp Ru nanoparticles begins from oxidation of Ru(001) to a RuO 2 (110) layer, and a subsequent CO oxidation occurs on RuO 2 (110). In a case of fcc Ru nanoparticles, the dominant facet is (111), which has the lowest surface energy.…”
Section: Co Oxidationmentioning
confidence: 97%
See 1 more Smart Citation
“…5c), a similar to the trend observed for Pt nanoparticles. 78 As mentioned above, some reports revealed that CO oxidation on hcp Ru nanoparticles begins from oxidation of Ru(001) to a RuO 2 (110) layer, and a subsequent CO oxidation occurs on RuO 2 (110). In a case of fcc Ru nanoparticles, the dominant facet is (111), which has the lowest surface energy.…”
Section: Co Oxidationmentioning
confidence: 97%
“…Very promising catalysts for this process are rhodium nanoparticles (oen supported). [107][108][109][110][111] It is worth mentioning that the reduction of nitro compounds can be oen easily monitored by simple UV-Vis absorption measurements. For example, in a case of reduction of 4-nitrophenol, an initial solution of 4-nitrophenol exhibits pale yellow color (the absorption band at 316 nm).…”
Section: Reduction Reactionsmentioning
confidence: 99%
“…The reduction process was carried out according to the chemical reactions (4) and ( 5), but the equilibria ( 6) and ( 7) must also be considered, in which either the hydration water of osmium nanoparticles or the one resulting from reaction can participate. The reduction of nitro derivatives with osmium compounds is very well known [32,33,66], but the study of this process on osmium nanoparticles with hydrogen gas is much less approached, the in-situ generation of molecular hydrogen especially with sodium borohydride being preferred [67,68].…”
Section: Reduction Of P-nitrophenol With Molecular Hydrogen With Osmium Nanoparticles-polypropylene Hollow Fibers Composite Membranesmentioning
confidence: 99%
“…The reduction of nitro derivatives with osmium compounds is very well known [32,33,66], but the study of this process on osmium nanoparticles with hydrogen gas is much less approached, the in-situ generation of molecular hydrogen especially with sodium borohydride being preferred [67,68].…”
Section: Reduction Of P-nitrophenol With Molecular Hydrogen With Osmium Nanoparticles-polypropylene Hollow Fibers Composite Membranesmentioning
confidence: 99%
“…Of course, the hydrogenation of nitro derivatives or related compounds with hydrogen gas in a non-aqueous heterogeneous medium is widely studied and accepted, especially when osmium complexes with various ligands are used as catalysts [65,66]. Also, the reduction of nitro derivatives in aqueous medium with atomic hydrogen (proton and electron) coming from a metal in contact with an acid or base is very much studied [67]. 3).…”
mentioning
confidence: 99%